Self-employment flows and persistance: A European comparative analysis - Mark Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We identify patterns of self-employment entry, exit and survival in a sample of EU countries and examine factors that explain individuals' self-employment experiences within and between countries. We estimate a range of models, including dynamic random effects models that endogenise the initial condition. Our results highlight similarities and differences between countries, and illustrate the importance of age and previous labour market experiences in determining self-employment flows. We also find a high degree of persistence in self-employment across countries, which is most pronounced in France and Germany and least pronounced in Spain. Our results suggest that flows into self-employment are positively associated with the strictness of employment protection legislation.
Keywords: J22; J24; J62; 330; self-employment; labour market dynamics; panel data; European Community Household Panel; dynamic random effects; Arbeitsmobilität; Selbstständige; Arbeitnehmerschutz; EU-Staaten